Protest and student mobilization in the Industrial University of Santander 2011-2012: the political opportunity (2017)
In this research a critical reconstruction of the processes and moments of protest and student mobilization is carried out in the context of the social confrontation unleashed by the initiative of the National Government of Colombia to reform the system of higher education. This research deepens the case of the Industrial University of Santander, Colombia. It employs a qualitative design by applying in-depth interviews to nine leader students visible in the institution, and analyzing the university context in 2011-2012 and the particularities of the situation inside the University. The results highlight a student movement of conjunctural political opportunity, the incorporation of cultural devices and technological means of symbolic efficiency. However, the merely nonconformist character resulted in the loss of grouping capacity by the students and in wasting